What Works in Supporting Women-Led Businesses? - Diego Ubfal (Institute of Labor Economics (IZA), 2024)
Innovative women entrepreneurs can be agents of change and offer novel solutions to global challenges. However, they face multiple barriers to growing their businesses. This paper reviews the literature on strategies to support women entrepreneurs in improving their business outcomes. It focuses on interventions designed to address four areas of constraints that influence their decisions and can impact their business performance: gaps in human capital, access to finance, access to technology and markets, and contextual factors such as legal and regulatory constraints, social norms, access to care, and gender-based violence. The review concludes that evidence of modest average treatment effects and heterogeneity in treatment effects across various interventions suggest the need for more precise targeting. The multiple constraints faced by women entrepreneurs necessitates testing different packages of interventions. Moreover, the successful implementation and adoption of proposed solutions require consideration of the contextual constraints that differentially affect women-led businesses. While the review highlights several interventions that show promise in supporting women entrepreneurs, significant gaps remain in the evidence concerning the most effective strategies.
Keywords: J16; L25; L26; O12; 330; literature review; gender; entrepreneurship; women-led businesses